Mapping of dwarf growth habit traits in apple (Malus pumila Mill.) using molecular markers and transcriptomics approaches - Mbulawa, Zama Thandekile Laureen (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhDAgric)--Stellenbosch University, 2020.